O-linked mucin-type glycosylation in breast cancer. (20th August 2018) - Burchell, Joy M.; Beatson, Richard; Graham, Rosalind; Taylor-Papadimitriou, Joyce; Tajadura-Ortega, Virginia
Abstract : Changes in mucin-type O-linked glycosylation are seen in over 90% of breast cancers where increased sialylation is often observed and a change from branched glycans to linear glycans is often seen. There are many mechanisms involved including increased/altered expression of glycosyltransferases and relocalisation to the endoplasmic reticulum of the enzymes responsible for the addition of the first sugar, N -acetyl-d -galactosamine. It is now becoming clear that these changes can contribute to tumour growth and progression by modulating the micro-environment through glycan-sensing lectins expressed on immune cells, by modulating interactions with tumour surface receptors and by binding to selectins. The understanding of how changes in mucin-type O-linked glycosylation influence tumour growth and progression reveals new potential targets for therapeutic intervention in the treatment of breast cancer.